Modular Parties, Customary Networks, and Constructivist Institutionalism - Tedi Erviantono; Nazrina Zuryani; Andrew Vandenberg (UIN Sunan Gunung Djati, 2024)
This article discusses the practice of modular parties as a discourse strategy that underpins patron-client relationships between politicians candidates, free-agent party functionaries, and mass voters. This practice departs from the conditions surrounding activism to mobilize voters in the context of: internal conflicts, parties that are too centralistic, the lack of regeneration, the de-ideologization of political parties, discourses about closed proportional elections, and the rampant phenomenon of cadres reconfiguring political parties. This article is based on qualitative interviews with groups of people in the networks of customary collectives, incumbent politicians, free agents, and political party functionaries in Bali. During the electoral process for the legislature in Bali, we conducted four interviews in 2021 and ten interviews in 2023. Bali is a province where the customary village-based activism is particularly important. The research is framed by constructivist institutionalism. We find that the network of customary collectivities and the relationship between free agents and incumbent politicians follows patron-client patterns. Within that pattern, actors innovate and communicate discourses about cultural preservation and the welfare of the customary collective. At the same time, they position the relevant leaders or parties as central actors who can provide solutions to the problems posed. This discourse strengthens ties between the mass of voters, free agents within the parties, and politicians or candidates. Such ties mobilize family-cum-community in the collectives of the villages and customary networks.